Variable X-chromosome inactivation and enlargement of pericentral glutamine synthetase zones in the liver of heterozygous females with OTC deficiency - Musalkova, Dita; Sticova, Eva; Reboun, Martin; Sokolova, Jitka; Krijt, Jakub; Honzikova, Jitka; Gurka, Jiri; Neroldova, Magdalena; Honzik, Tomas; Zeman, Jiri; Jirsa, Milan; Dvorakova, Lenka; et al. (Virchows Archiv, 2018)
Ornithine transcarbamylase (OTC) deficiency is an X-linked disorder that causes recurrent and life-threatening episodes of hyperammonemia. The clinical picture in heterozygous females is highly diverse and derives from the genotype and the degree of inactivation of the mutated X chromosome in hepatocytes. Here, we describe molecular genetic, biochemical, and histopathological findings in the livers explanted from two female patients with late-onset OTC deficiency. Analysis of X-inactivation ratios by DNA methylation-based assays showed remarkable intra-organ variation ranging from 46:54 to 82:18 (average 70:30, n = 37), in favor of the active X chromosome carrying the mutation c.583G>C (p.G195R), in the first patient and from 75:25 to 90:10 (average 82:18, n = 20) in favor of the active X chromosome carrying the splicing mutation c.663+1G>A in the second patient. The X-inactivation ratios in liver samples correlated highly with the proportions of OTC-positive hepatocytes calculated from high-resolution image analyses of the immunohistochemically detected OTC in frozen sections that was performed on total area > 5 cm2. X-inactivation ratios in blood in both female patients corresponded to the lower limit of the liver values. Our data indicate that the proportion of about 20-30% of hepatocytes expressing the functional OTC protein is not sufficient to maintain metabolic stability. X-inactivation ratios assessed in liver biopsies taken from heterozygous females with X-linked disorders should not be considered representative of the whole liver.
Keywords: glutaminsynthetasa; Ornithine Carbamoyltransferase Deficiency Disease; Biopsy; Glutamine synthetase; Humans; biopsie; Genotype; lidské chromozomy X; Sex Characteristics; Liver zonation; X Chromosome Inactivation; mužské pohlaví; Ornithine transcarbamylase; Chromosomes, Human, X; heterozygot; Glycogen storage; inaktivace chromozomu X; nemoc z nedostatku ornithinkarbamoyltransferázy; ženské pohlaví; Liver; genotyp; lidé; ornithinkarbamoyltransferasa; Heterozygote; X chromosome inactivation; Ornithine Carbamoyltransferase; játra; Male; pohlavní dimorfismus; Glutamate-Ammonia Ligase; Female